Online peer-group activism for thalassemia health education during the COVID-19 pandemic: a case study from East Java, Indonesia - Annette d'Arqom; Danti Nur Indiastuti; Zamal Nasution (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study aimed to measure the effectiveness of online peer-group activism to promote thalassemia prevention among high school students of East Java Indonesia. Design/methodology/approach - Twenty students were recruited as cadres and trained for thalassemia every weekend for four weeks, followed by creating health promotions via online media. The media was further disseminated among the students' peer groups for a week. The respondent's knowledge was measured before and after health promotion utilizing an online media mixed-methods approach that combined quantitative data using an online questionnaire and in-depth interviews for qualitative measurement. Descriptive and inferential analyses were performed using Graph Prism 5.00. Interview transcripts were analyzed to elaborate on the respondent's understanding of thalassemia. Findings - The respondents had good basic knowledge about thalassemia; however, it was not in-line with their understanding, which increased after the online health promotion activity. Therefore, this approach is useful for disseminating health issues during the COVID-19 pandemic and can be implemented for broadening respondents. Originality/value - This study showed the experience of online peer-group activism for thalassemia prevention in high school students. By empowering the peer group, health promotion is effective in increasing the knowledge and understanding of thalassemia. A similar approach can be proposed for other health issues.